Collaborating to Leverage American Heart Association's EmPOWERED to Serve Faith‐Based Networks for Methamphetamine and Stimulant Misuse Educational Campaign in Black and Hispanic Churches - Aviva K. Olsavsky; Brianna Boggs; Olubusola Dehinbo; Tariq Salem; Arika Cason; Malka Sierra; Julie Lay; Daniel Sunday; Kendra Huber; Stephen Scott; Crystal Natvig; Susan K. Mikulich‐Gilbertson; et al. (Psychiatric Research and Clinical Practice)
Objective In recent years, Black and Hispanic communities have been disproportionately impacted by growth in stimulant use disorders and overdose‐related mortality. Faith‐based institutions serve an important role in communities, and thus, community‐based interventions to enhance psychoeducation and reduce stigma are a promising area. The American Heart Association EmPOWERED to Serve program has developed health lessons through community‐based collaborations, including a video regarding stimulant use. Methods In collaboration with church partners, program staff and collaborators developed and implemented a 10‐min video in 12 church communities across several US states and in Puerto Rico. Implementation methods included virtual, hybrid, and in‐person forums. Six churches participated in a pre‐ and post‐video survey to assess effectiveness of the stimulant use disorder video for modifying attitudes toward substance use and for instilling knowledge about stimulant use disorders. Survey data (N = 478) were analyzed in SPSS utilizing Wilcoxon signed ranks for Likert scale responses or McNemar's tests for dichotomous data. Results Data suggested improvement in compassion for people with substance use and knowledge regarding stimulant use disorders. By contrast, sense of comfort in talking to loved ones with substance use and beliefs about substance use being a medical illness did not change following the video. Conclusions This work suggests that a brief 10‐min educational video lesson implemented by a trusted community leader is feasible and effective for reducing stigma and enhancing knowledge about substance use. Further research is required to design additional interventions and to assess for longitudinal effects.